BIOLOGI REPRODUKSI IKAN SEMBILANG (Plotosus canius) DI PERAIRAN PANTAI MAJAKERTA, INDRAMAYU, JAWA BARAT - Derry Muharam; Sulistiono; Etty Riani (Jurnal Teknologi Perikanan dan Kelautan, 2020)
Grey eel-tailed catfish (Plotosus canius) is one species of consumption fish that is quite popular in coastal communities. This study aims to analyze reproduction of the fish. Sampling was conducted monthly in Majakerta coastal area, Indramayu, West Java from February to April 2015. The total of samples observed were 98 fish, consisting of 65 males and 33 females. The observation was employed for sex ratio, gonad maturity stage, gonado somatic index, the size at first maturity, fecundity, and egg diameter of the fish. The result of this research shows that sex ratio of the fish was 2:1. Immature-mature fishes were found in each month. The size of first gonad maturity of the fish was 281 and 308,6 mm for male and female, respectively. Fecundity was 564-864, and according to oocyte diameter distribution, the fish was a partial spawner.